Highly active Cu-ZnO catalysts for the WGS reaction at medium–high space velocities: Effect of the support composition. (20th April 2017) - Price, C.; Pastor-Pérez, L.; le Saché, E.; Sepúlveda-Escribano, A.; Reina, T.R.
Abstract: Cu-ZnO based catalysts are the benchmark materials for the low-temperature WGS reaction. However, they present a crucial drawback which limits their application in portable devices: they only work under very low space velocities. In this study, we have developed a series of multicomponent Cu-ZnO catalysts able to work at relatively high space velocities with outstanding activity and stability. Different reference supports have been utilised with CeO2 -Al2 O3 being the most promising system. Overall, this work describes a strategy to design advanced Cu-based catalysts that can overcome the residence time restrictions in the WGS reaction. Highlights: Cost-effective Cu based catalysts for the WGS reaction. Excellent activity at medium–high space velocities. Robust catalysts – long term stability and tolerance to start-up/shutdowns cycles. Connecting physicochemical properties with engineering aspects. Boosted activity when CeO2 is added as promoter.